Peran Badan Pengawas Pemilihan Umum Kabupaten Lebak terhadap Pengawasan Pemasangan Alat Peraga Kampanye pada Pilkada Tahun 2024 - Syifa Ramadhani Fauziah; Mohamad Fasyehhudin; Ahmad Rayhan (Perspektif Administrasi Publik dan hukum, 2025)
Regional Head Elections (Pilkada) are democratic processes conducted to elect Governors and Deputy Governors, Regents and Deputy Regents, as well as Mayors and Deputy Mayors. The General Election Supervisory Agency (Bawaslu) is the authorized institution responsible for overseeing the implementation of elections, including their various stages. Campaigning is an integral component of the election process, during which candidates utilize campaign props (Alat Peraga Kampanye/APK) to promote themselves to the public. In Lebak Regency, numerous violations have occurred regarding the installation of such props, underscoring the critical role of Bawaslu Lebak in ensuring compliance. This study aims to examine the authority exercised by Bawaslu Lebak Regency in supervising the installation of campaign props during the 2024 regional elections and to identify the challenges encountered. The research employs the theory of authority and the theory of supervision, using an empirical juridical approach and an analytical descriptive specification. Primary data supported by secondary data were obtained through interviews and document analysis. The findings indicate that Bawaslu Lebak Regency implements both preventive and repressive supervisory measures. Preventive efforts include issuing advisories, conducting public outreach, and inter-agency collaboration, while repressive actions involve processing reports and findings of violations, as well as dismantling noncompliant campaign materials. The agency faces several obstacles, including low awareness among candidates and campaign teams regarding legal compliance, limited personnel for enforcement activities, resistance from various stakeholders, and the environmental issue of accumulated campaign waste.